Tasty sounds: crossmodal associations between chemosensory and auditory stimuli - Crisinel, A (2012)
The sensory evaluation of food products prior to and during ingestion is a vital process. As such, it is influenced by a variety of factors, comprising both contextual cues and sensory features of the food. The research presented in this thesis was designed to explore the crossmodal associations between auditory (musical notes) and chemosensory stimuli. The reported experiments revolve around three main goals. The first goal was to demonstrate the existence of reliable crossmodal associations between auditory and chemosensory stimuli. To this end, both implicit and explicit tasks were used. Specific pairings of basic tastes, flavours, and odours with musical notes were shown to be preferred, both in term of the pitch of the note and its timbre. The second goal was to suggest potential mechanisms or factors underlying these crossmodal associations. Two such factors were studied: familiarity and pleasantness. The familiarity with the chemosensory stimuli appeared not to affect much the crossmodal associations with musical notes. The pleasantness of the chemosensory stimuli was a main factor in the associations with the timbre of the note, but failed to satisfactorily explain the associations with the pitch of the note. Finally, the third goal was to evaluate the influence the congruence of auditory stimuli might have on the perception of simultaneously-presented chemosensory stimuli. Background soundtracks were shown to influence ratings of a food item on the bitter-sweet continuum. No such effect was observed when musical notes were presented simultaneously with odours. The research reported in this thesis constitutes the first detailed account of crossmodal associations between musical notes and a variety of chemosensory stimuli. The level at which such crossmodal associations might happen, as well as potential applications, are discussed, as well as possible directions for further research on the topic.